Say yes to Facebook and get your customers involved! Relationships in a world of social networks - Pereira, H.; Salgueiro, M. F.; Mateus, I. (Business Horizons, 2014)
This article investigates the role of Facebook in the establishment of relationships between brands and their fans, extending the link between relationship marketing and online consumer behavior. We explore what drives a user to connect with a brand profile on Facebook, to participate and interact with the community, and to share content published by brands on their own personal walls. To understand this relationship, we employed both qualitative and quantitative research techniques. The qualitative study was based on in-depth interviews of online marketing specialists and on a focus group comprised of Facebook users who were brand followers. The quantitative study was based on a structured questionnaire, which gathered responses from 650 Facebook brand followers. Results show that while Facebook users are willing to connect to brands on Facebook, they do not seem to interact or to frequently share brand content themselves. As a consequence, brands must strategize to establish a relationship with their brand profile fans.